2016
DOI: 10.1002/jat.3341
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the mechanism of non‐photocatalytically TiO2‐induced reactive oxygen species and its significance on cell cycle and morphology

Abstract: Titanium dioxide (TiO2 ) nanoparticles are widely used in daily human life, and were reported to elicit biological effects such as oxidative stress either generating reactive oxygen species (ROS) or causing cell necrosis without generating ROS, whose underlying molecular mechanisms are not yet known. In this study, the role of dissolved oxygen in TiO2 catalytic activity in dark environment, and long-term cytotoxic effects of TiO2 exposure were investigated. To determine the effect of dissolved oxygen, the anat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Generation of ROS was also found for TiO 2 NPs without UV activation, using toxicity tests on various mammalian cells 23 . From a more mechanism perspective, non-photoactivated induction of ROS by TiO 2 NPs via dissolved oxygen was reported in a recent study 24 . This implies that one possible toxicity mechanism of TiO 2 NPs might arise from ROS, and UV photoactivation can worsen this oxidative stress by increasing the level of ROS.…”
Section: Resultsmentioning
confidence: 92%
“…Generation of ROS was also found for TiO 2 NPs without UV activation, using toxicity tests on various mammalian cells 23 . From a more mechanism perspective, non-photoactivated induction of ROS by TiO 2 NPs via dissolved oxygen was reported in a recent study 24 . This implies that one possible toxicity mechanism of TiO 2 NPs might arise from ROS, and UV photoactivation can worsen this oxidative stress by increasing the level of ROS.…”
Section: Resultsmentioning
confidence: 92%
“…Since previous studies have reported that the treatment with various NPs, including titanium, resulted in the generation of ROS in multiple cell lines (Gali et al, 2016;Minai et al, 2013;Kundu et al, 2018) and the accumulation of intracellular ROS can induce COX-2 expression (Kundu et al, 2018;Nishanth et al, 2011), we examined whether TiO 2 -NPs accumulate intracellular ROS by measuring the fluorescence intensity of DCF-DA in PDL cells. The accumulation of ROS is induced by treatment of TiO 2 -NPs (2.5, 5 or 10 µg/mL) for 1 hr (Fig.…”
Section: Tio 2 -Nps Induce Generation Of Ros In Pdl Cellsmentioning
confidence: 99%
“…Work by Gali et al. 22 claimed that TiO 2 could generate O 2 − , HOO • , and HO − in the dark due to dissolved oxygen. Thus, it can be speculated that the oxygen from the environment and bacterial suspension could support the ROS generation from TiO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the effect of antibacterial property, the non-treated TiO 2 could generate the reactive oxygen species (ROS), producing O 2 − , HOO • , and HO − in the dark environment and HO • in the UV environment. 22 However, the effect of silane coupling agent on the mechanical and antibacterial properties of HPQM in the matrix is still not investigated.…”
Section: Introductionmentioning
confidence: 99%